Internal control and financial information of a State entity: Ministerio de Trabajo y Promoción del Empleo - Puma Hancco, Melissa Jennifer (2019)
Objective: To determine to what extent the lack of internal control under the components of "Law 28716" influences the reliability of the financial information of the Ministry of Labor and Employment Promotion, period 2014-2016. Method: It is a deductive, not experimental-transversal-correlational investigation. Results: The results of the survey of the personnel working in the Ministry of Labor and Employment Promotion, show that an adequate Internal Control System under the Control Environment components will positively improve the consistency of the information that sustains the active, passive and equity of the Statement of Financial Position. Conclusions: The Risk Assessment will improve the coherence and reliability of the information that sustains the income and expenses of the State of Management; the control activities will positively improve the opportunity of the patrimonial movement of the information that sustains the State of Changes in the Net Worth; the information and communication will positively improve the reasonableness of the cash movement information that sustains the Cash Flow Statement and the monitoring will improve that the information is free of substantial errors of the explanatory notes that support the Notes to the Financial Statements.